Psychological interventions in behavioral sleep medicine: An overview for clinicians and psychologists - Alessandra Giordano; Vincenza Castronovo; Alessandro Cicolin (Annals of Psychiatry and Treatment - Peertechz Publications, 2022)
Sleep medicine and psychology has a relatively long story to share. The multidisciplinary nature of sleep medicine requires that different specialists work together to diagnose and treat sleep disorders and improve subspecialty areas. In the last decades, various non-pharmacological therapies have been developed and demonstrated their efficacy. There are many non-pharmacological therapeutic available options for sleep disorders, including cognitive, behavioral, psycho-educational, and psychosocial interventions that could help clinicians to improve the quality of life of adult patients. Obstructive sleep apnea syndrome, insomnias, hypersomnias, circadian rhythm disorders, restless leg syndrome and parasomnias can be effectively taken care of, by an integrated approach with the support of sleep medicine psychologists. The paper aims to give a comprehensive view of psychological interventions for adults, in behavioral sleep medicine.